Comparing newly developed SNP barcode panels with microsatellites to explore population genetics of malaria parasites in the Peruvian Amazon - Cabrera-Sosa, Luis; Safarpour, Mahdi; Kattenberg, Johanna Helena; Ramirez, Roberson; Vinetz, Joseph M.; Rosanas-Urgell, Anna; Gamboa, Dionicia; Delgado-Ratto, Christopher (Frontiers in Genetics, 2024)
IntroductionMalaria molecular surveillance (MMS) can provide insights into transmission dynamics, guiding national control programs. We previously designed AmpliSeq assays for MMS, which include different traits of interest (resistance markers and pfhrp2/3 deletions), and SNP barcodes to provide population genetics estimates of Plasmodium vivax and Plasmodium falciparum parasites in the Peruvian Amazon. The present study compares the genetic resolution of the barcodes in the AmpliSeq assays with widely used microsatellite (MS) panels to investigate population genetics of Amazonian malaria parasites.MethodsWe analyzed 51 P. vivax and 80 P. falciparum samples from three distinct areas in the Loreto region of the Peruvian Amazon: Nueva Jerusalén (NJ), Mazan (MZ), and Santa Emilia (SE). Population genetics estimates and costs were compared using the SNP barcodes (P. vivax: 40 SNPs and P. falciparum: 28 SNPs) and MS panels (P. vivax: 16 MS and P. falciparum: 7 MS).ResultsThe P. vivax genetic diversity (expected heterozygosity, He) trends were similar for both markers: HeMS = 0.68–0.78 (p > 0.05) and HeSNP = 0.36–0.38 (p > 0.05). P. vivax pairwise genetic differentiation (fixation index, FST) was also comparable: FST-MS = 0.04–0.14 and FST-SNP = 0.03–0.12 (pairwise p > 0.05). In addition, P. falciparum genetic diversity trends (HeMS = 0–0.48, p < 0.05; HeSNP = 0–0.09, p < 0.05) and pairwise FST comparisons (FST-MS = 0.14–0.65, FST-SNP = 0.19–0.61, pairwise p > 0.05) were concordant between both panels. For P. vivax, no geographic clustering was observed with any panel, whereas for P. falciparum, similar population structure clustering was observed with both markers, assigning most parasites from NJ to a distinct subpopulation from MZ and SE. We found significant differences in detecting polyclonal infections: for P. vivax, MS identified a higher proportion of polyclonal infections than SNP (69% vs. 33%, p = 3.3 × 10−5), while for P. falciparum, SNP and MS detected similar rates (46% vs. 31%, p = 0.21). The AmpliSeq assay had a higher estimated per-sample cost compared to MS ($183 vs. $27–49).DiscussionThe SNP barcodes in the AmpliSeq assays offered comparable results to MS for investigating population genetics in P. vivax and P. falciparum populations, despite some discrepancies in determining polyclonality. Given both panels have their respective advantages and limitations, the choice between both should be guided by research objectives, costs, and resource availability.